The conversational Enlightenment : the reconception of rhetoric in eighteenth-century thought - Randall, David, 1972- (Edinburgh University Press, 2019)
Traces the spread of the concept of conversation during the Enlightenment, including the project of politeness, the fine arts, philosophy and public opinion. The book narrates this triumph of conversational style and thought partly as a succession to the oratorical rhetoric that characterized the Renaissance and partly as the victory of the only mode of speech that recognized women as women, and not as imitation men. It also rewrites Jürgen Habermas' history of the public sphere as the history of rational conversation.